(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Freedom of expression has always been emphasised as an essential basis for the democratic functioning of a society. The right to know, receive and impart information has been recognized within the right to freedom of speech and expression. A citizen has a right to know about the activities of the instrumentalities, the departments and the agencies of the State. Press plays a crucial role in dissemination of information. A free and vigilant Press is vital to restrain corruption and injustice by generat ing political discourse. Freedom of Press inevitably helps drive scientific progress which in turn propels innovation and economic prosperity. Al though the expression “Freedom of Press” has not been used in Article 19 but it is implicit in the right of freedom of speech and expression. It is the heart of social and political intercourse. Through this paper the authors try to emphasise the role of media on the basis of Aristotle’s ‘theory of Politics’. Further, want to consider the US position where there is an absolute Freedom of Press which has fostered innovation and also comment upon the various tests laid down by the Supreme Court of US to put reasonable restrictions upon such freedom.